The episode of the war between incas and chancas: a proposal about its construction and interpretation (Tzintzun, Revista de Estudios Históricos, 2016)
The article analyzes the version provided by the soldier chronicler of the16th century, Pedro Cieza de León in his Crhonicle of peru about the warbetween incas and chancas. This famous and particular battle is recountedby different Andean chroniclers. Since, after the inca victory began the Tawantinsuyu, or Inca Empire. Specifically, I focus to study the per-spective provided by Cieza and particular and significant elements thatprovided this story about the episode of that confrontation.
Keywords: guerra incas-chancas; Pedro Cieza de León; Tawantinsuyu